2022
DOI: 10.3390/biology11030385
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Lymphocyte-to-Monocyte Ratio (LMR), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR) and Tumor-Infiltrating Lymphocytes (TILs) in Left-Sided Colorectal Cancer Patients

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality worldwide. Novel markers are required in order to select high-risk patients and better adjust the treatment. Both peripheral and local markers of cancer-related inflammation (CRI) such as lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) and tumor-infiltrating lymphocytes (TILs) have been thoroughly investigated in recent years and deemed to be highly prognostic. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Furthermore, the predictive role of these markers has been proven in the cases of renal pathologies [ 32 , 33 , 34 ], cardiovascular pathologies [ 35 , 36 , 37 , 38 , 39 , 40 ], oncological pathologies [ 41 , 42 , 43 , 44 ], and, most recently, for COVID-19 patients [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the predictive role of these markers has been proven in the cases of renal pathologies [ 32 , 33 , 34 ], cardiovascular pathologies [ 35 , 36 , 37 , 38 , 39 , 40 ], oncological pathologies [ 41 , 42 , 43 , 44 ], and, most recently, for COVID-19 patients [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the systemic inflammatory biomarkers, the most accessible and easy to implement in current medical practice are hematological reports based on the total number of monocytes, neutrophils, lymphocytes, and platelets, respectively: monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic inflammatory index (SII), systemic Inflammation Response Index (SIRI), and aggregate index of systemic inflammation (AISI), whose predictive role has been demonstrated in the case of cardiovascular pathologies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], oncological pathologies [ 24 , 25 , 26 , 27 ], chronic kidney disease [ 28 , 29 , 30 ], and, more recently, in the case of COVID-19 patients [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that the low preoperative value of LMR may be a poor and significant predictor of clinical outcomes in patients with colorectal cancer ( 23 ). A retrospective study including 87 patients revealed that left-sided colorectal cancer patients with high preoperative LMR had a longer five-year overall survival ( 24 ). In patients with locally advanced rectal cancer, elevated LMR was prominently correlated with worse prognostic features and an independent factor for better OS ( 25 ).…”
Section: Discussionmentioning
confidence: 99%